Idiolekty pamięci – dziecięce dzienniki Zagłady. Od świadectwa do literatury - Wójcik-Dudek, Małgorzata (Stylistyka, 2019)
This article is an attempt to characterise diaries kept by children who were witnesses or victims of the Holocaust: Renia Knoll, Rutka Laskier, Dawid Rubinowicz, Dawid Sierakowiak and Anne Frank. The analysis of the texts made it possible not only to present their narrative diversity but above all to show the common grounds of children’s relations, which can be regarded as a kind of topos of children’s intimist experience of the Holocaust. According to the author, the theme of the Holocaust present in the analysed texts is also used in contemporary children’s literature, the authors of which deal with the issue of the Holocaust by styling stories into children’s war diaries. The author illustrates the relationship between authentic diaries and their stylisation, referring to the award-winning PamiętnikBlumki by Iwona Chmielewska, published in 2011